Signatory metabolomics biomarkers of stress, anxiety, and depression: a proof of concept for precision health among university students: A cross-sectional study - Nur Izzati Umar Zaman; Teh Lay Kek; Rohana Ahmad; Mohd Nur Fakhruzzaman Noorizhab; Mohd Salleh Rofiee; Richard Johari James; Norazmir Md Nor; Mawarni Mohamed; Teoh Sian Hoon; Parmjit Singh Arepar Singh; Roziah Mohd Janor; Sahol Hamid Abu Bakar; et al. (Precision and Future Medicine, 2023)
Purpose The highly competitive nature of tertiary education and the pressure to perform academically have increased psychological morbidity like emotional distress. Untargeted metabolomics was used to analyze serum samples of university students for biomarkers and perturbated metabolism due to stress, anxiety, and depression (SAD). Methods Depression, Anxiety, Stress Scale 21 (DASS-21) was used to assess the severity of SAD in university students. The metabolite fingerprint of each subject was obtained using liquid chromatography-mass spectrometry quadrupole time-of-flight (LC/MS QTOF). The signature metabolites for each trait were determined by projections to latent structures discriminant analysis (PLS-DA) with variable importance for the projection (VIP) score > 1.0 (P<0.05) and subjected to analysis using the area under the receiver operating characteristic curve (AUROC). Potential biomarkers with an area under the curve (AUC) value exceeding 0.65 were identified. Results Various groups of glycerophospholipids were upregulated in the studied traits. On the other hand, metabolites such as glycocholic acid was upregulated in depression, while hypoxanthine was upregulated in anxiety, and PE-Cer(d14:1(4E)/22:1(13Z)) was upregulated in stress. Conclusion To our knowledge, this is the first study to assess the relationship of the differentially expressed metabolites in university students of different categories of SAD using the DASS-21 screening tool in Malaysia as we move forward with precision health.